Does Opaqueness Make Equity Capital Expensive for Banks? (2014)
Bank managers often claim that equity is expensive, which contradicts the Modigliani-Miller irrelevance theorem. An opaque bank must signal its solvency by paying high and stable dividends in order to keep depositors tranquil. This signalling may require costly liquidations if the return on assets has been poor, but not paying the dividend might trigger a run. A strongly capitalized bank should keep substantial amounts of risk-free yet non-productive currency because the number of shares is high, which is costly. The dividend is informative of the state of the bank; rational depositors react to it.